2009
DOI: 10.1080/07420520902821077
|View full text |Cite
|
Sign up to set email alerts
|

Phase Angle of Entrainment in Morning‐ and Evening‐Types under Naturalistic Conditions

Abstract: Differences in morningness-eveningness among humans are commonly ascribed to circadian parameters, such as circadian period and responsivity to environmental time cues, as well as homeostatic sleep drive. Light is the primary synchronizer of the human biological clock, and if circadian differences exist between morning and evening types, they should have different phase angles of entrainment to the light/dark cycle; that is, morning and evening types should have different patterns of light exposure relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 40 publications
6
49
2
2
Order By: Relevance
“…Figure 1 shows the saliva melatonin profile over night. The mean DLMO was similar to a healthy population: 21.7 h ± 0.95 versus 20.1 ± 1.1 (morning types) and 21.7 h ± 0.95 versus 22.0 ± 1.2 (evening types) (Emens et al, 2009), but the phase angle of DLMO to bedtime was shorter than in this healthy population: 1.2 ± 1.5 hversus 2.2 ± 1.1 (morning types) and 1.2 ± 1.5 hversus 1.6 ± 1.1(evening types) (Emens et al, 2009;Lewy et al, 2006).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Figure 1 shows the saliva melatonin profile over night. The mean DLMO was similar to a healthy population: 21.7 h ± 0.95 versus 20.1 ± 1.1 (morning types) and 21.7 h ± 0.95 versus 22.0 ± 1.2 (evening types) (Emens et al, 2009), but the phase angle of DLMO to bedtime was shorter than in this healthy population: 1.2 ± 1.5 hversus 2.2 ± 1.1 (morning types) and 1.2 ± 1.5 hversus 1.6 ± 1.1(evening types) (Emens et al, 2009;Lewy et al, 2006).…”
Section: Resultsmentioning
confidence: 60%
“…The phase angle describes the relationship between the timing of the biological clock and the timing of external cues (Emens et al, 2009). The phase angle between the DLMO and sleep onset time was calculated by subtracting the DLMO time from the patient's bedtime.…”
Section: Melatonin Profilesmentioning
confidence: 99%
“…Exposure to light during this portion effectively shifts sleep timing to an earlier time, as determined by the phase response curve (PRC [64]). Lack of exposure to light during this pivotal phase for advancing sleep releases the "brakes" on the tendency to phase delay for individuals with taus longer than 24h [65][66][67].…”
Section: Phase Angle Of Entrainmentmentioning
confidence: 98%
“…The mechanism underlying this aspect of human entrainment has not yet been fully understood. It has been suggested that chronotype is likely associated with the endogenous period length because individuals whose clock is running with longer periods tend to be later chronotypes (Brown et al, 2005(Brown et al, , 2008Duffy et al, 2001;Emens et al, 2009;Pagani et al, 2010), but likely also with other properties of the clock driving the circadian rhythms, such as amplitude (Brown et al, 2008). The strength of the cue entraining the clock, i.e., the actual exposure to light, also plays an important role in maintaining the clock in a proper phase relationship with the external light/dark cycle ).…”
Section: Introductionmentioning
confidence: 99%